Pemanfaatan Scratch.mit.edu untuk Meningkatkan Literasi ICT Mahasiswa dalam Pembelajaran Matematika - Alivia Ivo Amirah Ghania Nasution; Yahfizham Yahfizham (JURNAL ILMIAH RESEARCH STUDENT, 2025)
Low ICT literacy among students is one of the obstacles in learning mathematics, especially in understanding abstract concepts. The use of technology-based learning media is one solution to improve students' ICT literacy. This study aims to determine the use of Scratch.mit.edu as a learning medium in improving students' ICT literacy in mathematics learning. The research method used is quantitative descriptive with data collection techniques in the form of questionnaires. The subjects of this study consisted of 10 students. The results of the study showed that students' responses to the use of Scratch.mit.edu were in the positive category, with the majority of respondents giving answers Strongly Agree and Agree. Thus, Scratch.mit.edu can be used as an alternative interactive ICT-based learning media to support mathematics learning.